Assessing the role of college as a sustainability communication channel. Issue 7 (6th November 2017) - Lertpratchya, Alisa P.; Besley, John C.; Zwickle, Adam; Takahashi, Bruno; Whitley, Cameron Thomas
Abstract : Purpose: The purpose of this study is to assess the effectiveness of higher education institution as a sustainability communication channel. The theory of planned behavior was used to examine the degree to which a student's tenure at a large university with active and visible sustainability initiatives is associated with changes in views about sustainability and changes in reported sustainability behaviors. Design/methodology/approach: This study involved a campus-wide online survey on undergraduate students at a large mid-western university. A direct measurement approach to the theory of planned behavior was used to measure changes in attitudes, normative beliefs, perceived behavioral controls and self-reported behaviors on five different environmental sustainability behaviors. Findings: Overall findings support the notion that higher education institutions can be effective communication channels for sustainability issues, as students who have been in college for a longer period of time reported somewhat more positive attitudes, normative and efficacy beliefs and more sustainable behaviors. Practical implications: By measuring specific components of the theory of planned behavior, this study provides insights on specific areas in which campaigns targeting college students in different college years could become more effective. Originality/value: Few studies have assessed college as an effective sustainability communication channel despite the fact that it is potentially a powerful channel to reach a large population at their critical age. This study also measures specific components to sustainability behaviors by using the theory of planned behavior as a guiding framework.